Om att inte vara en typisk flygvärdinna - Petersson, Magdalena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1997)
The wide-spread image or the air hostess is created from a normative idea of women. As such it contains the common dualism or motherliness on the one hand and sexual availability on the other. Even though their profession has undergone enormous changes during its fifty years, young air hostesses today in many ways judged by the standards formed in the 1940’s. The visibility interent in their daily work-life creates expectations around their physical appearances and also has the function of a disciplinary practice.